What Designers Want: Needs of Interactive Application Designers - Fernandez, Roland; Inkpen, Kori; Robertson, George (Symposium on Visual Languages and Human-Centric Computing (VLHCC 2009), 2009)
Designers’ extensive software needs have not been adequately documented in the research literature, and are poorly supported by software. Without appropriate tools to support their needs, designers have difficulty knowing the best way to evolve the look and feel of interactive applications they are designing. In order to inform the design of new tools for interactive application design, we used a grounded theory approach to find out what designers’ needs are when designing such applications. This paper reports our findings (20 designer needs) from content analysis of five types of artifacts: surveys, Blend discussion list emails, Dreamweaver forum entries, Flash forum entries, and interviews with ten designers. These 20 needs were then validated in follow-up interviews and focus group sessions. The results of this work revealed trends regarding the importance of each need and show that flow is one of the most important needs.